Resistance to Wheat streak mosaic virus identified in synthetic wheat lines - Shoup Rupp, Jessica L.; Simon, Zachary G.; Gillett-Walker, Beth; Fellers, John P. (My University, 2014)
Wheat streak mosaic virus (WSMV) is an important pathogen in wheat that causes significant yield losses each year. WSMV is typically controlled using cultural practices such as the removal of volunteer wheat. Genetic resistance is limited. Until recently, no varieties have been available with major resistance genes to WSMV. Two resistance genes have been derived from Thinopyrum intermedium through chromosome engineering, while a third gene was transferred from bread wheat through classical breeding. New sources of resistance are needed and synthetic wheat lines provide a means of accessing genetic variability in wheat progenitors. A collection of wheat synthetic lines was screened for WSMV resistance. Four lines, 07-SYN-27, -106, -164, and -383 had significant levels of resistance. Resistance was effective at 18 °C and virus accumulation was similar to the resistant control, WGGRC50 containing Wsm1. At 25 °C, resistance was no longer effective and virus accumulation was similar to the susceptible control, Tomahawk.
Citation: Shoup Rupp, J. L., Simon, Z. G., Gillett-Walker, B., & Fellers, J. P. (2014). Resistance to Wheat streak mosaic virus identified in synthetic wheat lines. Retrieved from http://krex.ksu.edu
Keywords: Virus resistance; Wheat streak mosaic virus; Synthetic wheat lines; Wheat